MIRAGE - Afifah, Meutia
Mirage is an experimental painting that aims to represent the situation from the context of today's daily reality using an approach to space and everyday objects. Along with the development of advanced science and technology, human life is inseparable from two realities that have merged into everyday life and become important, especially during a pandemic. The existence of the internet, especially social media, shifts the meaning of something real and not real. This phenomenon then triggers the author's thinking to question the perception of human consciousness that lives between these realities in response to a reality and an illusion. The author tries to play with the reality of the mirage that painting can produce. The creation process that has been carried out by the author includes; examine the theory of art as a representation and discourse about reality and mirage imagery as well as the collection of images and visual studies, then proceed with the process of making sketches on canvas and coloring and the use of casting techniques on canvas and the surface of everyday objects. The author tries to transform this scope into a pattern that is owned by painting which is able to present a very illusory nature but at the same time is able to present the concrete nature of paint that is more real. Then it will then respond to objects around everyday space that have other dimensional qualities. This work is also an attempt to celebrate the chaos of reality and the way to coexist with disorder. The use of mediums in this work include; oil paints for and acrylic paints on canvas with a pouring technique that responds to surrounding objects and canvas displays that respond to everyday spaces and objects. In the end, the resulting work then made the writer aware that the reality that was formed in the painting actually only existed in a flat surface. But still able to produce 3 levels of juxtaposition. The first is the effort to create images that exist in the depiction of everyday objects on the canvas that are in contact with the concrete pouring paint. Second, pouring paint that responds to everyday objects that exist. The third is the placement of the canvas which seems to be correct when placed in everyday spaces.